2016
DOI: 10.1136/postgradmedj-2016-133997
|View full text |Cite
|
Sign up to set email alerts
|

Gastric adenocarcinoma: the role ofHelicobacter pyloriin pathogenesis and prevention efforts

Abstract: Gastric cancer is the third most common cause of cancer deaths in the world, prompting high-risk countries like South Korea and Japan to establish nationwide screening programmes. Helicobacter pylori is linked to the majority of gastric adenocarcinoma cases and to the vast majority of non-cardia gastric adenocarcinomas. Several studies have demonstrated the effectiveness of 'test-and-treat' programmes for H. pylori infection to prevent gastric cancer in high-risk populations. While this strategy has gained mom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…10 It is known to cause gastritis and gastric ulcer through chronical inflammation, which may later develop into cancerous tissues. 11,12 Despite the important association between H. pylori and gastric cancer, the genomic landscape of H. pyloripositive gastric tumors remains largely unknown. There is some evidence that H. pylori could activate the oncogenic drivers EGFR and Akt signaling, both oncogenic drivers, in gastric cancer cells.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…10 It is known to cause gastritis and gastric ulcer through chronical inflammation, which may later develop into cancerous tissues. 11,12 Despite the important association between H. pylori and gastric cancer, the genomic landscape of H. pyloripositive gastric tumors remains largely unknown. There is some evidence that H. pylori could activate the oncogenic drivers EGFR and Akt signaling, both oncogenic drivers, in gastric cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…H. pylori is a helix‐shaped Gram‐negative bacterium usually found in the stomach 10 . It is known to cause gastritis and gastric ulcer through chronical inflammation, which may later develop into cancerous tissues 11,12 . Despite the important association between H. pylori and gastric cancer, the genomic landscape of H. pylori‐positive gastric tumors remains largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…[ 12 ] Laird-Fick et al . [ 13 ] reported that Helicobacter pylori infection is the direct cause of at least 75% of gastric carcinoma worldwide. Helicobacter pylori was proven to disrupt the tight junctions between gastric cells, insert genetic material into them, and suppress the host immune responses.…”
Section: Risk Factors Of Gastric Carcinomamentioning
confidence: 99%
“…[ 15 ] Moreover, Helicobacter pylori infection was reported to induce DNA methylation and histone modification in the gastric epithelial cells with the final result of the development of gastric carcinoma. [ 13 ]…”
Section: Risk Factors Of Gastric Carcinomamentioning
confidence: 99%
“…Almost half of the world's population has been infected with H. pylori, particularly in developing countries where people are more susceptible to the infection, mostly due to the large populations and poor sanitation (2,3).…”
mentioning
confidence: 99%